Design and simulation of Solar Powered Automated Dual Rotor Mechanism for Sugarcane Harvesting - Sachin S Raj; R A Kapgate; Harshal Darekar; Krishna Darade; Nikita Dongare; Sarthak Narode (International Journal of Robotics and Automation in Mechanics, 2026)
Sugarcane being the vast cultivated cash crop of India’s agricultural economy has undoubtedly one of the most difficult harvesting processes. The existing mechanisms to harvest sugarcane are costly and are not affordable by rural based farmers. In this project a novel design mechanism is suggested that would serve the purpose of harvesting with least manpower, being cost effective and serving the purpose of cutting, stripping, sorting and loading of the harvested sugarcane. The machine consists of a dual stage rotary conveyor belt mechanism built on a sturdy box-frame consisting of a dual wire-cut mechanism setup. One on the top to chop the shoot of the crop and other at the bottom for the root removal. The DC motors for powering the wire cut mechanism are run by a 9 v 9 amp battery powered through a monocrystalline solar panel while the conveyor belts run with the power sourced from the tractor. The bottom belt is responsible for the sugarcane stem and the top rack conveyor roller transports the chopped shoot leaves to discard. An output of 3 acres per day of harvest is expected from the machines efficiency which can be attached to the normal tractor in a common farmers farmland. Mechatronic devices such as a load cell to monitor the overall load capacity of the harvested sugarcane, steel brushes to wear away the stems from leaves and blowers to discard excess leaves are placed in sequence of the loader design. This projects works on a prototype design and focuses on simulation of the mechanical components using solidworks software. The automatic sugarcane loading conveyor belt system is an innovative agricultural solution designed to streamline the post-harvest handling process by automating the transfer of cut sugarcane into transport vehicles or storage units. This system eliminates the need for manual loading, significantly reducing labor, time, and physical effort while improving operational efficiency and safety.
Keywords: Automated sugarcane harvester; Simulation; Twin roller mechanism; solar powered; wire cut